2009
DOI: 10.1177/003335490912400510
|View full text |Cite
|
Sign up to set email alerts
|

Improvements in Access to Care for Vulnerable Children in California between 2001 and 2005

Abstract: SYNOPSISObjective. We examined population changes in access to care for children in California during a period of major efforts to improve access to care for children.Methods. We used cross-sectional data on 36,010 children aged 0-19 years from the 2001 and 2005 California Health Interview Survey to assess population changes in access to care. We assessed changes in access by individual risk factors and a composite risk profile. [CI] 1.07, 1.12) and dental visit (OR51.11, 95% CI 1.08, 1.14). Children were slig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
8
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 20 publications
4
8
0
Order By: Relevance
“…One mediator of this disparity is insurance status, as non-White individuals are more likely to be uninsured or underinsured, limiting access to care for these patients 24. California has sought to provide universal access to health care for children, potentially mitigating the effects of this disparity 25. Although our center does not consider patient insurance when accepting new referrals, many pediatricians limit the number of Medicaid patients they see due to unsustainably low reimbursement rates 26.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One mediator of this disparity is insurance status, as non-White individuals are more likely to be uninsured or underinsured, limiting access to care for these patients 24. California has sought to provide universal access to health care for children, potentially mitigating the effects of this disparity 25. Although our center does not consider patient insurance when accepting new referrals, many pediatricians limit the number of Medicaid patients they see due to unsustainably low reimbursement rates 26.…”
Section: Discussionmentioning
confidence: 99%
“…24 California has sought to provide universal access to health care for children, potentially mitigating the effects of this disparity. 25 Although our center does not consider patient insurance when accepting new referrals, many pediatricians limit the number of Medicaid patients they see due to unsustainably low reimbursement rates. 26 This results in shortages of health care providers, including pediatricians, in underserved communities, which in turn delays necessary care.…”
Section: Discussionmentioning
confidence: 99%
“…and dental reconstruction must be covered by insurance according to state law SB-630, so nearly all patients in our care are eligible for affordable orthodontic care (Stevens et al, 2007;Health Care Coverage, 2009;Stevens et al, 2009). However, this care is often not covered by low-cost health plans nationwide.…”
Section: Discussionmentioning
confidence: 99%
“…In California, children, including undocumented individuals, have near-universal access to medical and dental coverage. In addition, medically necessary orthodontic care and dental reconstruction must be covered by insurance according to state law SB-630, so nearly all patients in our care are eligible for affordable orthodontic care (Stevens et al, 2007; Health Care Coverage, 2009; Stevens et al, 2009). However, this care is often not covered by low-cost health plans nationwide.…”
Section: Discussionmentioning
confidence: 99%
“…Latina women are exposed to the healthcare system much more frequently than men [23], thereby increasing the need to address barriers, which may obstruct their access to care. Though the literature is limited with regard to studies that focus on Latina immigrants specifically, some studies have shown that Latina immigrants in particular are less likely to have health insurance coverage as well as to not have a usual source of care as compared to both white and US-born Latina women [24, 25]. Other studies have shown that Latina immigrants are hesitant to seek health care services due to structural and non-structural barriers such as language, lack of health insurance, procrastination, embarrassment, and lack of proper documentation [2628].…”
Section: Introductionmentioning
confidence: 99%